Superlattice by charged block copolymer self-assembly - Jimin Shim (Nature Portfolio, 2019)
Understanding the phase behavior of charged block copolymers may potentially lead to unexplored self-assembled morphologies. Here, the authors report the preparation of ion-containing diblock copolymers featuring a superlattice state varying between disordered and lamellar morphologies depending on the charge density.